1992
DOI: 10.1200/jco.1992.10.11.1781
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic spinal cord compression secondary to lung cancer.

Abstract: Despite a short survival, early diagnosis and immediate treatment is crucial because it may preserve the gait function in 97% of lung cancer patients who develop malignant spinal cord compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Functional outcome was acceptable in the entire cohort of 73 patients, 68.5 % (50 of 73) of the patients were able to walk 4 weeks after decompression; 51.5 % (17/33) of nonambulatory patients before operation regained the ability to walk. 74-84 % of patients were able to walk after surgery [2,5] and 22-68 % of nonambulatory patients became ambulatory again in other studies [5,7].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Functional outcome was acceptable in the entire cohort of 73 patients, 68.5 % (50 of 73) of the patients were able to walk 4 weeks after decompression; 51.5 % (17/33) of nonambulatory patients before operation regained the ability to walk. 74-84 % of patients were able to walk after surgery [2,5] and 22-68 % of nonambulatory patients became ambulatory again in other studies [5,7].…”
Section: Discussionmentioning
confidence: 82%
“…Maranzano et al [4] stated that the choice of radiotherapy alone or surgery in MSCC depended on accurate patient selection. Recently, only a few studies specifically addressed surgical treatment of MSCC in lung cancer [5][6][7]. Generally speaking, good surgical results are obtained from lung cancer patients with MSCC, while who may benefit from decompressive surgery remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There was 1 RCT, 37 2 prospective cohort trials, 14,22 and 14 retrospective case series. 2,3,6,7,15,17,19,23,[25][26][27][28]31 As regards neurological outcomes for laminectomy alone without instrumentation for stabilization, Class II data are provided by Young et al 37 In their RCT of 29 patients, laminectomy followed by radiotherapy (RT) was compared with RT alone for the treatment of spinal metastases. Inclusion criteria were a neurological symptom, myelographic extradural block, and tissue diagnosis of metastasis.…”
Section: Posterior Laminectomy With and Without Instrumentationmentioning
confidence: 99%
“…3 In a follow-up study, Bach et al evaluated outcomes in patients experiencing MSCC due to lung carcinoma and found similar data when comparing the efficacy of PL with that of RT (PL = 48%, RT = 46%, PL+RT = 67%). 2 Chaichana et al 6 (78 patients) evaluated the use of PL on metastatic epidural spinal cord compression based on tumor location and the patient's circumstances. 6 Of the 55 patients who were able to ambulate preoperatively, 24 (44%) underwent a PL.…”
Section: Posterior Laminectomy With and Without Instrumentationmentioning
confidence: 99%
“…Nadal jednak toczą się dyskusje dotyczące wyboru najbardziej efektywnej formy frakcjonowania dawki, dawki całkowitej czy też sposobu kojarzenia RT z innymi metodami leczenia, jak terapią izotopową, lekami modulującymi metabolizm tkanki kostnej czy leczeniem operacyjnym [5,6]. Z powodu odmienności okolic anatomicznych, w których występuje przerzut, różnej liczebności przerzutów (całkowita masa przerzutów) u danego chorego oraz różnorodności sposobów frakcjonowania dawki i jej specyfikacji w RT, jak również niedoskonałości w metodach oceniających ból u chorych, niejednokrotnie trudno jest wskazać najlepszy sposób napromieniania [7][8][9][10].…”
unclassified